75 Principles of Conscious Leadership: Inspired Skills for 21st Century Business - Michael Schantz (Bandon, OR Robert D. Reed Publishers, 2008)
This book came as Schantz's response to a deep calling to create one volume that contained the best of the principles, practices and conscious skills for the leaders of the 21st Century organization. Schantz distilled the learning from his coaching, mastermind, studies in leadership, spirituality and psychology, plus many years of professional management experience, and observation. 75 Principles of Conscious Leadership is a compendium of the conscious skills of leadership, human communication, human motivation, and mentoring. It is designed to be used as a manual, or handbook, of time-honored disciplines of effective communication and spiritual consciousness, foundational to leadership as a life's practice. Woven through all of the principles are the qualities of compassion, service, and contribution. As the book portrays, the principles and practices of leadership comprise a discipline, a lifelong experience learned through continual refinement. Mastering effective leadership requires commitment, as all transformation starts from within. They are available to anyone who embraces them into their professional lives and relationships.
Keywords: Business; Leadership; Psychology; Productivity; Nonfiction; Spirituality; Leadership and Mentoring (HRM2073-N)